Modelling the dynamic compressive response of syntactic foam with hierarchical cell structure. (November 2021) - Fan, Zhiqiang; Zhang, Fei; Zhang, Bingbing; He, Tianming; Xu, Peng; Cai, Xuanming
Abstract: Rate-dependent mechanical response of fly ash cenospheres polyurethane syntactic foams (CPSFs) with hierarchical cell structure was examined through dynamic compression tests. Quasi-static compression strength and specific energy absorption varied in the range of 9.5–29.5 MPa and 4.8–13.0 MJ/m 3 within the density of 0.5–0.7 g/cm 3 . The thermal conductivity coefficient of CPSFs increased from 0.08 W/m/K to 0.13 W/m/K with density, while the specific heat capacity varied in a narrow range of 0.9–1.07 J/g/K. At high strain rates the strength and plateau stress of CPSFs with density of 0.6 g/cm 3 increased 25%–39% and 13%–43%. The proposed foam is comparative potential in civil engineering according to its thermal insulation performance and excellent shock dissipation properties. Due to complicated microstructure, CPSFs exhibited different strain rate sensitive behaviors in the initial collapse stage and the stable collapse stage. A constitutive relation was developed to describe dynamic stress-strain response which includes the elastic stage, the initial collapse stage characterized by nonlinear stress increasing and decreasing process, the platform stage and the densification stage. The predictions shown good accordance with the experimental results in wide strain rate range. Highlights: Rate-dependent mechanical response of fly ash cenosphere polyurethane syntactic foam was examined and modelled. Hierarchical cell structure lead to different dominating failure patterns and rate dependency at different stages. A new constitutive framework was established to describe four phases stress-strain response.